2019
DOI: 10.1111/1751-7915.13382
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR interference‐mediated gene regulation in Pseudomonas putida KT2440

Abstract: SummaryTargeted gene regulation is indispensable for reprogramming a cellular network to modulate a microbial phenotype. Here, we adopted the type II CRISPR interference (CRISPRi) system for simple and efficient regulation of target genes in Pseudomonas putida KT2440. A single CRISPRi plasmid was generated to express a nuclease‐deficient Cas9 gene and a designed single guide RNA, under control of l‐rhamnose‐inducible Prha BAD and the constitutive Biobrick J23119 promoter respectively. Two target genes were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
(59 reference statements)
1
20
1
Order By: Relevance
“…In both cases, CRISPRi was highly efficient, with less than 1% remaining reporter protein signal. Similarly, targeting plasmid GFP reporter gene in Pseudomonas putida decreased fluorescence intensity to background levels (Kim et al 2020). In this study, flow cytometry analysis revealed substantial drop of plasmid-borne GFPUV fluorescence (~70%) in P. sonchi SBR5 expressing dCas9 and gfpUV targeting sgRNA, but about 30% of the reporter signal remained (Table 2).…”
Section: Discussionsupporting
confidence: 52%
“…In both cases, CRISPRi was highly efficient, with less than 1% remaining reporter protein signal. Similarly, targeting plasmid GFP reporter gene in Pseudomonas putida decreased fluorescence intensity to background levels (Kim et al 2020). In this study, flow cytometry analysis revealed substantial drop of plasmid-borne GFPUV fluorescence (~70%) in P. sonchi SBR5 expressing dCas9 and gfpUV targeting sgRNA, but about 30% of the reporter signal remained (Table 2).…”
Section: Discussionsupporting
confidence: 52%
“… TF Promoter Inducer(s) Reported pros, cons and main applications in P. putida Ref. (s) Positively regulated induction systems XylS Pm m -toluate and derivatives + High expression levels + Extensively characterized + Cheap inducers − Catabolite repression − Dose-dependent response in absence of inducer metabolization pathways − Bimodal response − Leaky expression 28 , 49 , 63 , 130 139 Applications: Expression of I- sceI , dCas9 , trfA , the λ red operon, and recombinases in genome engineering tools; expression of toxic genes for controlled autolysis; production of recombinant antibody fragments and p -coumaric acid RhaRS P rhaB l -rhamnose + No catabolite repression + No metabolization of rhamnose: dose-dependent response + Tight regulation + Non-toxic inducer − Inhomogeneous response at intermediate inducer levels − Expensive inducers 132 , 138 , 140 , 141 Applications: Expression of dCas9 for CRISPRi and Cre for genomic deletions; production of p -coumaric acid AraC P BAD l -arabinose + Characterization + No catabolite repression + No metabolization of arabinose: dose-dependent response + Tight regulation + Non-toxic inducer − Inhomogeneous response at intermediate inducer levels − Poor arabinose uptake without AraE transporter − Expensive inducers 132 , 142 , 143 Applications: Production of p -coumaric acid Negatively regulated induction systems LacI Plac, PlacUV5, Ptac, Ptrc Lactose, isopropyl β...…”
Section: Constructing Novel Genetic Circuits: the Sum Is More Than Itmentioning
confidence: 99%
“…A linear response of downregulation levels of a chromosomally expressed msf·gfp was observed as a function of the inducer (3‐ m Bz) concentration. This feature represents a substantial improvement to previously CRISPRi‐based approaches, which did not allow for titratable gene downregulation (Kim et al , ), sometimes exhibiting high leakiness (> 50%) in the absence of the corresponding inducers (Tan et al , ). Importantly, we also demonstrated the ability to simultaneously downregulate three genes in P. putida with this system.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, two alternative SpdCas9-based CRISPRi systems were developed and explored in Pseudomonas species (Sun et al, 2018;Kim et al, 2020). Both systems were demonstrated to be functional for repression of genes encoding fluorescent proteins, and Kim et al (2020) also employed CRISPRi for metabolic engineering via gene repression by depleting the GlpR regulator to enhance the glycerol-dependent synthesis of mevalonate. Other examples on the development of CRISPRi systems have been reported for P. aeruginosa (Peters et al, 2019;Qu et al, 2019) and P. fluorescens (Noirot-Gros et al, 2019).…”
Section: Introductionmentioning
confidence: 99%